PERKAWINAN DINI PADA KELUARGA MUSLIM DI KABUPATEN CIREBON PERSPEKTIF YURIDIS SOSIOLOGIS - Mohamad Rana; Tajul Arifin (Mahkamah : Jurnal Kajian Hukum Islam, 2022)
Based on data from the Sumber-Cirebon PA regarding the application for marriage dispensation and the Cirebon Regency DPPBP3A data, it shows the high number of early marriages in Muslim families in Cirebon Regency. This research aims to determine the factors causing early marriage and the effectiveness of the provisions of Law no. 1 of 1974 Article 7 paragraph (1) related to the minimum age limit for marriage in Muslim families in Cirebon Regency. The approach used is qualitative with descriptive analytical method. The classified data was then analyzed using a sociological juridical approach, and then concluded. As for the results of the research, that the factors causing the high rate of early marriage are because there are factors behind it and the ineffectiveness of the minimum age limit for marriage stipulated by law.